AN ANALYSIS OF "ORIFLAME" WOMAN PERFUME ADVERTISEMENTS - Novantia Amandhita Fajar; Nina Setyaningsih (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2015)
Slogan and image usually represent a product in an advertisement. Theslogan consists of phrases or sentences, while the image consists of people or elsewith the background. This research was conducted to find out the tools to conveythe message in Oriflame perfume advertisements and to discover the hiddenmessages by using those tools in the advertisements. Searle’s illocutionary actstheory (1977) and Peirce's semiotics theory (1931) were used as frameworks foranalysis. A descriptive qualitative was used to analyze the data. The result showsthat from verbal tool analysis, there are 17 illocutionary acts found in the taglinesand body copies of the advertisements. The first illocutionary act found in the datais assertive. It is because the advertiser wants their product to be known and topersuade the readers by using information, description, claim, and statement. Thesecond is directive because the advertiser gives command to the readersespecially woman to use the perfume. From non verbal tool analysis, theresearchers found signs in each background image which then were turned intoobject and interpretant through a cognition process. From verbal and non verbaltools, the researchers discovered the hidden messages of the Oriflame perfumeadvertisements. The conclusion is that the advertiser created different images ofeach advertisement. The images support the tagline and the body copy ofadvertisement. The advertiser wants the consumers to be able to choose their ownperfume based on their characteristics or what they want to be like.